The Role of Self-Compassion and Emotion Regulation: How to Predict Life Satisfaction in Covid-19 Survivors? - Naflah Aulia Prameswari Putri; Setiasih Setiasih (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The Covid-19 phenomenon in Indonesia has an impact on the entire community, especially on Covid-19 survivors. The impact felt is not only physical, but also psychological aspects that can affect their life satisfaction. The purpose of this study was to examine the role of self-compassion and emotion regulation on the life satisfaction of Covid-19 survivors. The research method uses a quantitative approach, and the sampling technique uses purposive sampling technique. The measuring instruments used in this study are the Self-Compassion Scale (SCS), Emotional Regulation Questionnaire (ERQ), and Satisfaction Scale with Life (SWLS). Data analysis used multiple linear regression tests. The results showed that self-compassion and emotion regulation can predict life satisfaction with a significant value of 0.000. However, self-compassion has no significant effect on life satisfaction (p>0.05), while emotion regulation has a significant positive correlation with life satisfaction (p=0.000). Another variable that was tested and had an association with life satisfaction was marital status. The effect of self-compassion and emotion regulation on life satisfaction is 18%. It can be concluded that it is important for individuals to have self-compassion that helps to accept the situation that occurs and emotion regulation that can increase one's life satisfaction to have better psychological well-being.Fenomena Covid-19 yang ada di Indonesia memberikan dampak pada seluruh masyarakat terutama pada penyintas Covid-19. Dampak yang dirasakan selain fisik yaitu aspek psikologis yang dapat mempengaruhi kepuasan hidup mereka. Tujuan dari penelitian ini untuk menguji peran dari self-compassion dan regulasi emosi terhadap kepuasan hidup penyintas Covid-19. Metode penelitian menggunakan pendekatan kuantitatif dan teknik sampling menggunakakan teknik purposive sampling. Alat ukur yang digunakan dalam penelitian ini yaitu Self-Compassion Scale (SCS), Emotional Regulation Questionnaire (ERQ), dan Satisfaction Scale with Life (SWLS). Analisis data menggunakan uji regresi linier berganda. Hasil penelitian menunjukkan bahwa self-compassion dan regulasi emosi dapat memprediksi kepuasan hidup dengan nilai signifikansi 0,000. Akan tetapi, self-compassion tidak memiliki pengaruh signfikan terhadap kepuasan hidup (p>0,05), sedangkan regulasi emosi memiliki korelasi positif yang signifikan terhadap kepuasan hidup (p=0,000). Variabel lain yang diuji dan memiliki asosiasi dengan kepuasan hidup yaitu status pernikahan. Pengaruh self-compassion dan regulasi emosi terhadap kepuasan hidup sebesar 18%. Dapat disimpulkan bahwa penting bagi individu untuk memiliki self-compassion yang membantu untuk menerima situasi yang terjadi serta regulasi emosi yang dapat meningkatkan kepuasan hidup seseorang agar memiliki kesejahteraan psikologis yang lebih baik.